Clergy and royal service: the case of king Fernando's chancery - Coelho, André Madruga (2017)
This study aims to analyse the participation of medieval clergy in royal administration through the example of the ecclesiastics mentioned in the documents of the chancery of king Fernando I of Portugal. For this, we shall analyse: 1) the ecclesiastics in the royal household; 2) the ecclesiastics with offices in the royal bureaucracy